Reflexiones sobre el patrimonio cultural de la salud en Latinoamérica (2010)
This paper analyzes the experiences and initiatives to promote the cultural heritage of Latin America s health; in order to provide adequate means to motivate the debate from a historical and socio-political reading of urban space; to extend his eyes to see and understand the city from its landscape.